Gender disparities in acute coronary syndrome. Issue 5 (May 2015) - Ghadri, Jelena R.; Sarcon, Annahita; Jaguszewski, Milosz; Diekmann, Johanna; Bataiosu, Roxana D.; Hellermann, Jens; Csordas, Adam; Baumann, Lukas; Schöni, Aline A.; Lüscher, Thomas F.; Templin, Christian
<x xml:space="preserve">Abstract</x> Aims The aim of the present study was to analyze gender disparities in a large cohort of acute coronary syndrome (ACS) patients from the Zurich Acute Coronary Syndrome (Z-ACS) Registry. Methods Gender disparities in ACS were examined. The primary endpoint included in-hospital death rate, and the secondary endpoint major adverse cardiac and cerebrovascular events (MACCEs) at 30-day follow-up. Furthermore, independent predictors for MACCEs and death were identified. Results In total, 2612 patients with ACS were identified. Out of these, 23% were women. The mean age was higher in women (68.6 ± 12.2; P < 0.001). Troponin-T on admission (1.33 ± 4.64 vs. 1.19 ± 3.04 μg/l; P = 0.002) and N-terminal of the prohormone brain natriuretic peptide on admission (3456.2 ± 7286.7 vs. 1665.6 ± 4800.6 ng/l; P < 0.001) were higher in women compared with men. Single-vessel disease was more common in women (44.9 vs. 39.7%; P = 0.023) and, conversely, multivessel disease was more prevalent in male patients as compared with their female counterparts (59.4 vs. 54.4%; P = 0.029). At discharge, men were more likely prescribed statins (89.4 vs. 85.2%; P = 0.004). Overall mortality and MACCEs were similar for both genders. In women, peak creatine kinase and peak C-reactive protein emerged as independent predictors for MACCEs and SBP on admission, and maximal C-reactive protein and use of glycoprotein IIb/IIIa inhibitors (GPIIb/IIIa) as strong independent predictors for in-hospital death. Conclusion The present results suggest a closing gap in short-term outcome and improvement in cardiac care between women and men. Nonetheless, differences in treatment strategies continue to exist, particularly pertaining to statin regimens at discharge, which might potentially have a powerful impact on long-term outcomes and gender disparities.